Antibacterial effects of Andrographis paniculata extract, Curcuma domestica extract, chloramphenicol and their combinations on the growth of Salmonella typhi bacteria - Rahmadi, Agus; Elya, Berna; Suryadi, Herman; Prasetio, Nisrina Putri; Kamaruzzaman, Mohd Amir (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Typhoid fever caused by Salmonella typhi remains a serious health threat. Although standard treatment with antibiotics such as chloramphenicol has helped reduce mortality rates, bacterial resistance to this antibiotic is increasing. New treatment approaches are urgently needed, including combining antibiotics with natural compounds from medicinal plants, such as Andrographis paniculata and Curcuma domestica. This study aimed to compare the antibacterial effects of A. paniculata extract, C. domestica extract, chloramphenicol, and their combinations on the growth of S. typhi. This in vitro experimental study used the disc diffusion method to evaluate antibacterial activity. Antibacterial activity tests were performed against S. typhi using discs soaked in 70% ethanol extract solutions of A. paniculata and C. domestica, chloramphenicol, and their combinations. Inhibition zones were measured after incubation for 24 hours at 37°C. Chloramphenicol showed the strongest antibacterial activity with a mean inhibition zone of 28.33 ± 0.58 mm. Single extracts of A. paniculata and C. domestica had relatively weak antibacterial activity (inhibition zones of 9.67 ± 1.15 mm and 9.83 ± 0.29 mm) and there was no significant difference between them (p>0.05). Combinations of extracts with chloramphenicol showed increased antibacterial activity compared to single extracts (inhibition zones of 23.17 ± 1.26 mm for A. paniculata + chloramphenicol and 21.00 ± 2.65 mm for C. domestica + chloramphenicol) and there were significant differences between combinations and single extracts (p<0.05), but still lower than single chloramphenicol and statistically significant (p<0.05). Although combining medicinal plant extracts with chloramphenicol increased antibacterial activity compared to single extracts, it did not exceed single chloramphenicol.